1994
DOI: 10.1007/bf00795731
|View full text |Cite
|
Sign up to set email alerts
|

Doppler echocardiographic evaluation of left ventricular diastolic function after surgical correction of atrial septal defect during childhood

Abstract: Transmitral flow was studied using Doppler echocardiography with the A/E ratio as a parameter of left ventricular diastolic function in 21 patients (ages 2.5-30.0 years) who had undergone early surgical correction of an isolated secundum type atrial septal defect (ASD) compared to a healthy cohort of 21 subjects. Pre- and postoperative M-mode recordings were compared in 12 of the 21 patients to evaluate the effect of operation on interventricular septal motion (IVS) and left ventricular (LV) and right ventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This contrasts to a study where ventricular diastolic function was completely normal in patients operated during childhood. 12 These authors have found no mechanical sequels of right ventricular volume overload in the follow-up after repair. The data in our patients differ considerably, with diastolic dysfunction of the left ventricle occurring in half of our patients.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This contrasts to a study where ventricular diastolic function was completely normal in patients operated during childhood. 12 These authors have found no mechanical sequels of right ventricular volume overload in the follow-up after repair. The data in our patients differ considerably, with diastolic dysfunction of the left ventricle occurring in half of our patients.…”
Section: Discussionmentioning
confidence: 87%
“…When repair is performed electively while patients are young, right ventricular hypertrophy and dilation may often resolve within six months to one year after operation. 11,12 It has been suggested that the decrease in right ventricular size correlates with the length of follow-up. 13 Our data show that almost always there is a postoperative regression of cavity size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 22 Abnormal septal motion occurs in the majority (up to 86%) of patients with an ASD, 17 19 but this appears to resolve with exercise 23 24 and after surgical repair. 25 Following surgical repair of an ASD, echocardiographic assessment suggests an increase in left ventricular volume, 25 and in one study left ventricular function was normal both before and one year after repair. 8 Persistence of right ventricular dilatation after ASD repair is commonly reported, 8 affecting more than 80% of patients up to five years after repair.…”
Section: Discussionmentioning
confidence: 98%
“…Systolic and diastolic dysfunction among children with congenital heart defects in pre and postoperative periods is a well-known problem, described by a number of investigators [7][8][9][10][11][12][13]. These alterations depend on various factors, e.g., relaxation, contractility, compliance and filling of the atria and ventricles [14][15][16].…”
Section: Introductionmentioning
confidence: 99%